Comparison of durability parameters of in-situ concrete obtained from local ports - Fill, Byron A.
This paper deals with the comparison of durability parameters namely chloride ingress and carbonation and as an end result compare exposure regions and to evaluate to over-all durability state of the structure. This study involves samples cored from the ports located in Batangas City, Batangas; Davao City, Davao and Matnog, Sorsogon. This research aims to establish chloride ingress and carbonation depth history of in-situ concrete core samples available at hand that were obtained from different local ports, compare the chloride ingress, concentration and carbonation of. different ports and provide an end-result assessment about its condition. This research is done through different test methods which are: Silver Nitrate (Colorimetric) Spray Test, Ion Chromatography Test and Phenolphthalein Spray Test. Comparison were made on the basis of core location and chloride concentration played a vital role in the evaluation. The results proved that the concrete exposed to the marine environment specifically the parts submerged on the tidal zone are the ones showing relatively higher chloride concentration hence depth of chloride ingress on those regions are higher. Samples show significant concentration of chloride ingress but these never reached the entire length of sample thus ingress hasn't reached the embedded metal and corrosion hasn't started. When it comes to carbonation, only 2 samples shows signs of carbonation which is less than 45% of the length of the sample both of which are cored in the tidal regions, which in terms of the entirety of the structure will be insignificantly small. It can then be concluded on this research that the ports wherein samples were taken and being tested are still structurally sound in the basis of durability considering effects of corrosion through chloride ingress and carbonation.